Enhancing roasted pepper quality sustainably: Impact of biodegradable mulches - Marcos Guerra; Miguel Angel Sanz; Álvaro Rodríguez-González; Pedro Antonio Casquero (Journal of Agriculture and Food Research)
Plastic mulching is a prevalent agricultural practice offering various benefits, including increased soil temperature, reduced weed pressure, enhanced moisture conservation, and improved crop yields. However, the widespread use of non-biodegradable plastic mulches poses environmental challenges. In response, soil-biodegradable plastic mulches (BDMs) have emerged as eco-sustainable alternatives, particularly crucial for high-quality products like roasted pepper. Roasted pepper is a processed vegetable crop awarded the European recognition of 'Protected Geographical Indication' as 'Pimiento Asado del Bierzo'. This study compares the impact of non-degradable mulches (NDMs), BDMs, and bare ground cultivation (BGC) on the quality of roasted peppers. Results reveal that peppers grown under plastic mulches exhibit superior colouration, uniformity, and reduced charred remains compared to BGC. Additionally, ease of skin peeling is enhanced with plastic mulches, promising increased productivity in industrial processing. Particularly, BDM films, promoting sustainable agriculture practices, offer premium quality while mitigating environmental risks. These findings underscore the potential of plastic mulches, especially BDMs, in enhancing crop quality and sustainability in vegetable production, particularly in the context of high-quality food products.